Reliability and validity of the Chinese version of the Work-Family-School Role Conflicts Scale among nurses - Rhayun Song; Caifu Li; Lei Wang; Xianwen Li; Zanhua Zhou; Lijuan Xu (International Journal of Nursing Sciences, 2021)
Objective: To translate and validate the Chinese version of the Work-Family-School Role Conflicts Scale (WFSRCs-S) among nurses with multiple roles. Methods: A sample of 233 registered nurses pursuing an advanced degree was recruited from 8 university hospitals in 5 cities in China from March to July 2016. The original scale of WFSRCs-S was translated into Chinese and revised to reflect cultural meaning, using standard translation methodology, and its reliability and validity were assessed. Results: The content validity index of the 12-item WFSRCs-S-Chinese was 0.83, and the item level of content validity index ranged from 0.79 to 1.00. The exploratory factor analysis yielded a three-factor solution (work-school-to-family role conflict, family-school-to-work role conflict, and work-family-to-school role conflict) and explained 71.9% of the total variance for WFSRCs-S-Chinese. The Cronbach’s α coefficients for the total scale and the three sub-scales were 0.87, 0.79, 0.78, and 0.87. The confirmatory factor analysis revealed that the measurement model was satisfied, and the test-retest reliability of WFSRCs-S-Chinese was 0.85. The WFSRCs-S-Chinese score was positively associated with burnout (r = 0.36, P < 0.001) and negatively related to role-related social support (r = −0.18, P = 0.046), thereby establishing concurrent validity. Conclusion: The reliability and construct validity of the WFSRCs-S-Chinese suggest that this scale could be useful to assess inter-role conflicts among nurses with multiple roles in China.